(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
Reported herein are the design, development and investigation for antibacterial and antifungal studies of a novel series of substituted quinoline analogues bearing pyrazole moiety. Acetanilide derivatives were prepared from the reaction of various anilines with acetyl chloride. Cyclization of these acetanilide derivatives (Vilsmeier-Haack reaction) using phosphorus oxychloride and dimethyl formamide afforded corresponding 2-chloroquinoline-3-carbaldehyde compounds (1a-1l). Titled molecules were synthesized through treatment of 1a-1l with hydrazine hydrate to afford corresponding 1H- pyrazolo [3,4-b] quinolines (2a-2l). All the synthesized analogues were recrystallized and characterized through FTIR, 1H-NMR and mass spectroscopy. All analogues were screened for antibacterial activity against gram-positive (Staphylococcus aureus) and gram-negative (Escherichia coli) bacteria while antifungal activity against Candia albicans, and Aspergillus niger by disc diffusion method. Compounds 2c, 2e, 2h, 2k, and 2l exhibited promising antibacterial and antifungal activity when compared with standard drugs ciprofloxacin and fluconazole, respectively. Thus, these studies suggest that quinoline derivatives bearing pyrazole moiety are interesting scaffolds for the development of novel antibacterial and antifungal agents.